Impact of FDI on Unemployment in Transition Countries: Panel Cointegration Approach - Zdravković, Aleksandar; Đukić, Mihajlo; Bradić-Martinović, Aleksandra (Industrija, 2017)
This paper examines the relationship between FDI inflow per capita and unemployment rates in 17 transition countries over the period 2000-2014. It aims at testing the premise, usually suggested by policy makers, that higher attraction of FDI in transition countries results in inevitable unemployment reduction. The empirical analysis contributes to the existing literature applying panel cointegration approach in testing and assessing long-run impact of FDI on unemployment, as an alternative to typical panel analysis that examine contemporaneous relations. The evidence from seven performed panel cointegration tests provide the mixed results, while the Fully Modified and Dynamic OLS panel estimations indicate that FDI and unemployment are most likely not cointegrated. The inconclusiveness of the empirical evidences gives the argument in support of the general conclusion that long-run impact of FDI on unemployment in transition countries is either very loose or does not exist.
Keywords: Foreign direct investments; Unemployment; Transition countries; Panel; Cointegration